0.9(6x+4)=0.7-(x-3)

Simple and best practice solution for 0.9(6x+4)=0.7-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.9(6x+4)=0.7-(x-3) equation:


Simplifying
0.9(6x + 4) = 0.7 + -1(x + -3)

Reorder the terms:
0.9(4 + 6x) = 0.7 + -1(x + -3)
(4 * 0.9 + 6x * 0.9) = 0.7 + -1(x + -3)
(3.6 + 5.4x) = 0.7 + -1(x + -3)

Reorder the terms:
3.6 + 5.4x = 0.7 + -1(-3 + x)
3.6 + 5.4x = 0.7 + (-3 * -1 + x * -1)
3.6 + 5.4x = 0.7 + (3 + -1x)

Combine like terms: 0.7 + 3 = 3.7
3.6 + 5.4x = 3.7 + -1x

Solving
3.6 + 5.4x = 3.7 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
3.6 + 5.4x + x = 3.7 + -1x + x

Combine like terms: 5.4x + x = 6.4x
3.6 + 6.4x = 3.7 + -1x + x

Combine like terms: -1x + x = 0
3.6 + 6.4x = 3.7 + 0
3.6 + 6.4x = 3.7

Add '-3.6' to each side of the equation.
3.6 + -3.6 + 6.4x = 3.7 + -3.6

Combine like terms: 3.6 + -3.6 = 0.0
0.0 + 6.4x = 3.7 + -3.6
6.4x = 3.7 + -3.6

Combine like terms: 3.7 + -3.6 = 0.1
6.4x = 0.1

Divide each side by '6.4'.
x = 0.015625

Simplifying
x = 0.015625

See similar equations:

| 9x-1=3x+4t | | (x-6)2+(y-1)2=81 | | 15x=840 | | 186000=400X | | 10y+5x=500 | | 10y-5x=500 | | (x+4)2+(y-9)2=144 | | 3y-4=-14 | | -5x+3y=-47 | | 9x^6(9x^5-9)= | | 9x^5-9= | | 2.3b=1.5x | | 9a+54=80 | | 4x+-2+3x=12 | | 169x^4=0 | | 7x=3x+23 | | 44=-8X-45 | | 20+4g=5g | | 2(32+w)=120 | | y*x= | | x^2+12x-589=0 | | 2d-13d+4d+-11d=11 | | x^2=12x-589 | | 50+15+x=180 | | 12y=.25 | | 3(x+1)=6(x+6) | | 10y+32=82 | | 3cos(x)+9=7 | | 2.8x-0.4y+1.5=0 | | 7.1x+3.4y-3.6=0 | | 42+z=81 | | 8.1x+9.7y-6.6=0 |

Equations solver categories